On the relationship between anxiety and error monitoring: a meta-analysis and conceptual framework - Moser, Jason; Moran, Tim; Schroder, Hans; Donnellan, Brent; Yeung, Nick (Frontiers in Human Neuroscience, 2013)
Research involving event-related brain potentials has revealed that anxiety is associated with enhanced error monitoring, as reflected in increased amplitude of the error-related negativity (ERN). The nature of the relationship between anxiety and error monitoring is unclear, however. Through meta-analysis and a critical review of the literature, we argue that anxious apprehension/worry is the dimension of anxiety most closely associated with error monitoring. Although, overall, anxiety demonstrated a robust, “small-to-medium” relationship with enhanced ERN (r = −0.25), studies employing measures of anxious apprehension show a threefold greater effect size estimate (r = −0.35) than those utilizing other measures of anxiety (r = −0.09). Our conceptual framework helps explain this more specific relationship between anxiety and enhanced ERN and delineates the unique roles of worry, conflict processing, and modes of cognitive control. Collectively, our analysis suggests that enhanced ERN in anxiety results from the interplay of a decrease in processes supporting active goal maintenance and a compensatory increase in processes dedicated to transient reactivation of task goals on an as-needed basis when salient events (i.e., errors) occur.